Active Participation of Students in the Education Process - Kaltsas , Evangelos Panagiotis; Gkaintartzi , Anastasia (Research Highlights in Language, Literature and Education Vol. 6, 2023)
In the present study, the methods confused with the active participation of the students in the educational procedure, and the ways students can participate in it, are examined and presented. Active involvement of students in school concerns both the educational procedure and the activities taking place at school, social or otherwise. Student involvement at school can have multiple aspects, going from initially taking place inside the classroom to eventually taking place over the entirety of school life. The study consists of a review of Greek and international bibliography. The study’s material consists of articles related to the topic found in Greek and international databases such as Google Scholar, the Hellenic Academic Libraries Association (HEAL-Link). Participation by students in school activities fosters self-respect and confidence. The youngsters begin to sense that they are valued, heard, and taken into account. The children who are being encouraged are in a position to develop their own ideas and learn new skills, and they also feel more comfortable expressing their beliefs in every aspect of their lives. Student participation in school, either inside the classroom, or inside the school life in general, provides the children with supplies for their future and experiences, thus making them active citizens.